Implementasi Strategi Transformasi Digital Berbasis Analisis SWOT melalui Modul Inovasi Pengelolaan Manajerial pada UMKM Tahu Goreng ABA - Satrio Ahmadtul Firdaus Romadhoni; Dikie Egie Nugraha; Agus Hermawan; Agung Winarno (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital technology has changed the operational paradigm of Micro, Small, and Medium Enterprises (MSMEs), including the culinary sector. However, most MSMEs still face limitations in adopting digital-based management systems. This study aims to implement a SWOT analysis-based digital transformation strategy through the development of a Managerial Innovation Module for the